Numerical analysis of MICP treated sand based on bio-chemo-hydro model - Li, Delong; Chen, Shengzhe; Gao, Xing (Frontiers in Bioengineering and Biotechnology, 2024)
Microbially Induced Calcite Precipitation (MICP) represents an environmentally friendly and innovative soil grouting technology. Involving intricate biochemical processes, it poses challenges for a thorough investigation of factors influencing microbial grouting effectiveness through experimentation alone. Consequently, A three-dimensional numerical model was developed to predict the permeability of bio-grouting in porous media. The numerical model is validated by comparing its results with test results available in the literature. The validated model is then used to investigate the effects of variation bacterial solution concentration, cementation solution concentration, grouting rate and grouting time on grouting effectiveness. It was founded that the remediation effect was positively correlated with the bacterial solution concentration and the number of grouting. An increased grouting rate enhanced the transport efficiency of reactants. Additionally, the concentration of cementation solution exhibited no significant effect on the reduction of calcium carbonate yield and permeability.